Aislamiento e identificación de Listeria monocytogenes y Listeria spp. en embutidos secos obtenidos en mercados de la ciudad de La Plata, Argentina - Pellicer, Karina (2002)
A total of 60 samples of dry sausages were analyzed (50 of "salami" and 10 of "chorizo" "candelario" type) obtained at random in markets authorized for their commercialization, for the purpose of evidencing the presence of bacteria of the genus Listeria (Listeria monocytogenes and Listeria spp.). The results obtained in salami were the following: 10 (20%) isolates of Listeria spp., were characterized: 1 (2%) strain as L. monocytogenes type 1, 7 (14%) strains as L. innocua, 2 (4%) strains as L. welshimeri. In chorizo candelario type 6 (60%) isolates of Listeria spp., were characterized: 2 (33%) strains as L. monocytogenes type 1 and 4 (66%) strains as L. innocua. The total percentages of isolations were: 26.6% of Listeria spp., 5% of L. monocytogenes type 1, 18.3% of L. innocua and 3.3% of L. welshimeri. In conclusion, we consider that methodologies of control must be developed and implemented in order to guarantee the inocuity of these products